6(3b+2)+2=b-20

Simple and best practice solution for 6(3b+2)+2=b-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3b+2)+2=b-20 equation:


Simplifying
6(3b + 2) + 2 = b + -20

Reorder the terms:
6(2 + 3b) + 2 = b + -20
(2 * 6 + 3b * 6) + 2 = b + -20
(12 + 18b) + 2 = b + -20

Reorder the terms:
12 + 2 + 18b = b + -20

Combine like terms: 12 + 2 = 14
14 + 18b = b + -20

Reorder the terms:
14 + 18b = -20 + b

Solving
14 + 18b = -20 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
14 + 18b + -1b = -20 + b + -1b

Combine like terms: 18b + -1b = 17b
14 + 17b = -20 + b + -1b

Combine like terms: b + -1b = 0
14 + 17b = -20 + 0
14 + 17b = -20

Add '-14' to each side of the equation.
14 + -14 + 17b = -20 + -14

Combine like terms: 14 + -14 = 0
0 + 17b = -20 + -14
17b = -20 + -14

Combine like terms: -20 + -14 = -34
17b = -34

Divide each side by '17'.
b = -2

Simplifying
b = -2

See similar equations:

| X/2*30=1000 | | -6+12x=102 | | 5x^2+5y^2-6x-6y+5=0 | | -27+8=-12+c+20 | | 54b+72=252 | | -14+x=-22 | | [v-3]=-7 | | 8b+4=92 | | -83=4(1-4b)-7 | | 6+3x=6-6x | | -13c+7=-32 | | -3(x-8)=5(x+8) | | -7(2n-2)+2=100 | | 8y-12=52 | | 37+5=35+7 | | (f+9)=39 | | -11(-x+10)=-(-x-30) | | 5(f-32)=180 | | X-1=9x+7 | | 3x/5-2/3=4x | | 6(2x-7)=-114 | | 5+32f=180 | | 3+4k=115 | | 7sen^2+5sin(-x)cosx=2-2cos^2x | | 6y^2+7-5=0 | | 3+4k=-115 | | 83-2x=20+19x | | 4x/3=33 | | 14+3(2x-5)=22 | | 3x^2-4.4x=9.6 | | 5(2x+3)-4(2-3x)=2(2+3x) | | 7p+4=-3 |

Equations solver categories